Fatty acid synthase inhibitor orlistat induces apoptosis in T cell lymphoma: Role of cell survival regulatory molecules - Kant, Shiva; Kumar, Ajay; Singh, Sukh Mahendra (Biochimica et biophysica acta, 2012)
De novo fatty acid synthesis catalyzed by fatty acid synthase (FASN) is crucial for tumor cell survival. Thus therapeutic targeting of FASN is considered as a novel antineoplastic strategy. However, little is understood in this respect regarding malignancies of hematological origin. The present investigation was therefore, undertaken to study the molecular mechanisms of the antitumor action of FASN inhibitor orlistat (tetrahydrolipstatin) using a murine model of a T cell lymphoma. The antitumor efficacy of orlistat was investigated in vitro by estimating cell survival by MTT assay and apoptosis by Wright Giemsa, TUNEL, Annexin-V/PI staining and % DNA fragmentation. Generation of reactive oxygen species (ROS) in tumor cells was studied using fluorescence microscopy. Expression of genes and proteins was carried out by RT-PCR and western blot analyses respectively. FASN and CPT-1 activity was estimated by spectrophotometer. Cytokines expression was analyzed by ELISA. We report that inhibition of FASN with its specific inhibitor orlistat manifests tumor-specific inhibition of cell survival, accompanied by induction of apoptosis. Orlistat-treated tumor cells showed an altered ROS generation, shift in cytokine balance and modulated expression of cell survival regulatory molecules like HSP70, Bcl2, p53, PUMA, Caspase-3 and CAD. It was observed that IFN-γ mediates orlistat-dependent modulation of FASN expression. In this study, we report some of the so far unexplored novel aspects underlying the molecular mechanisms associated with orlistat-dependent modulation of tumor cell survival. These observations will help in designing antineoplastic therapeutic protocols using orlistat against malignancies of hematological origin. ► Fatty acid synthase (FASN) inhibitor orlistat inhibits survival of tumor cells by inducing apoptosis. ► FASN inhibition causes modulation of cell survival regulatory molecules. ► 1. Shift of cytokines balance & ROS generation is implicated.